Fast-disappearing destinations: the relationships among experiential authenticity, last-chance attachment and experiential relationship quality. Issue 7 (2nd July 2020) - Wu, Hung-Che; Cheng, Ching-Chan; Ai, Chi-Han; Wu, Tsung-Pao
Abstract: This paper explores the relationships among experiential authenticity, the dimensions of last-chance attachment (last-chance dependence, last-chance identity, last-chance affect and last-chance social bonding) and the dimensions of experiential relationship quality (experiential trust, experiential satisfaction and experiential loyalty). A convenience sample of 505 tourists in Malé, Banana Reef, Artificial Beach and Sun Island of the Maldives was surveyed. The results indicate (a) a positive effect of experiential authenticity on last-chance dependence, last-chance identity, last-chance affect and last-chance social bonding, respectively; (b) positive effects of last-chance dependence, last-chance identity and last-chance affect on experiential satisfaction; (c) a positive effect of experiential satisfaction on experiential trust; and (d) positive effects of both experiential trust and experiential satisfaction on experiential loyalty. The implications of this study for academics and fast-disappearing destination management are discussed.